Cytokines and HCV-Related Disorders - Poupak Fallahi; Clodoveo Ferri; Silvia Martina Ferrari; Alda Corrado; Domenico Sansonno; Alessandro Antonelli (Clinical and Developmental Immunology)
Cytokines are intercellular mediators involved in viral control and liver damage being induced by infection with hepatitis C virus (HCV). The complex cytokine network operating during initial infection allows a coordinated, effective development of both innate and adaptive immune responses. However, HCV interferes with cytokines at various levels and escapes immune response by inducing a T-helper (Th)2/T cytotoxic 2 cytokine profile. Inability to control infection leads to the recruitment of inflammatory infiltrates into the liver parenchyma by interferon (IFN)-gamma-inducible CXC chemokine ligand (CXCL)-9, -10, and -11 chemokines, which results in sustained liver damage and eventually in liver cirrhosis. The most important systemic HCV-related extrahepatic diseases—mixed cryoglobulinemia, lymphoproliferative disorders, thyroid autoimmune disorders, and type 2 diabetes—are associated with a complex dysregulation of the cytokine/chemokine network, involving proinflammatory and Th1 chemokines. The therapeutical administration of cytokines such as IFN-alpha may result in viral clearance during persistent infection and reverts this process.